2021
DOI: 10.1055/s-0041-1724015
|View full text |Cite
|
Sign up to set email alerts
|

Embolization in Trauma: Review of Basic Principles and Techniques

Abstract: Trauma is the leading cause of death in patients younger than 45 years. Over the last decade, there has been a progressive paradigm shift toward a nonoperative management of many blunt and penetrating injuries, placing interventional radiology in the forefront in this critical field. Transcatheter embolization is an established technique that plays a significant role in the modern treatment of traumatic injuries of the extremities, pelvis, and solid organs. The purpose of this article is to review the updated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
0
13
1
Order By: Relevance
“…In this setting, it is widely acknowledged that the embolic choice should be at the discretion of the operator. 23 However, regression analysis in this study showed that the use of a non-selective embolisation technique was significantly protective of mortality, and non-selective embolisation was used significantly more in unstable patients in our cohort. Both selective and nonselective embolisation have been shown to be effective in pelvic haemorrhage management, and the use of either is generally at operator discretion.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…In this setting, it is widely acknowledged that the embolic choice should be at the discretion of the operator. 23 However, regression analysis in this study showed that the use of a non-selective embolisation technique was significantly protective of mortality, and non-selective embolisation was used significantly more in unstable patients in our cohort. Both selective and nonselective embolisation have been shown to be effective in pelvic haemorrhage management, and the use of either is generally at operator discretion.…”
Section: Discussioncontrasting
confidence: 53%
“…In assessing the type of treatment given to patients, the type of embolic agents used in this study varied between an even mix of gelatin sponge, coils, or a combination of the two. In this setting, it is widely acknowledged that the embolic choice should be at the discretion of the operator 23 . However, regression analysis in this study showed that the use of a non‐selective embolisation technique was significantly protective of mortality, and non‐selective embolisation was used significantly more in unstable patients in our cohort.…”
Section: Discussionmentioning
confidence: 58%
“…For patients with ongoing arterial bleeding from pelvic fractures angiographic embolization can be used [Wong and Bucknill, 2017]. Embolization is a procedure to control bleeding in a particular area by using a catheter to access the effected blood vessel and use either a balloon or haemostatic agents to partially block the vessel to control bleeding [Lopera, 2021]. This can be used as a first line intervention in haemodynamically unstable pelvic ring injuries [NICE, 2017].…”
Section: Embolizationmentioning
confidence: 99%
“…This can be used as a first line intervention in haemodynamically unstable pelvic ring injuries [NICE, 2017]. Angiography is when a contrast is inserted into blood vessels under X ray so that the site of bleeding in a particular blood vessel can be located [Lopera, 2021]. It cannot be used to treat arterial bleeding from multiple sources [Parry et al 2020].…”
Section: Embolizationmentioning
confidence: 99%
“…However, arterial injury may still produce a blush, and angioembolization of arterial source of bleeding may then be pursued for hemorrhage control. A strategy of selective or supra-selective embolization techniques to the injured vessels may be used [ 23 , 24 ], but more centrally located or named vessels should be avoided for total occlusion and subsequent ischemia. Given the dual supply by the liver (portal and arterial), even extensive embolization may be well tolerated.…”
Section: Adjunct Role Of Angioembolization To Operative Managementmentioning
confidence: 99%